2001
DOI: 10.1076/jcen.23.5.671.1247
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Consequences of Severe Closed Head Injury on Episodic Memory

Abstract: This is the first systematic investigation of the very long-term effects of severe closed head injury (CHI) on objective measures of memory, and the first to employ both a normal control group and an 'other injury' control group consisting of spinal cord injury (SCI) patients. The CHI group displayed significantly poorer performance on every memory measure, and the effect sizes were large. This impairment in episodic memory is neither due to pre-injury nor post-injury differences between CHI and normal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 38 publications
1
30
0
3
Order By: Relevance
“…Most studies with patients who sustained moderate to severe TBI have found impaired memory (Blachsteni et al, 1993;Millis and Ricker, 1994;Vakil, 2005;Vanderploeg et al, 2001). In addition, recovery of learning and memory functions has been found to be slower compared to other TBI cognitive abilities (Lezak, 1979), with deficient learning and memory persisting after moderate to severe TBI (Zec et al, 2001). TBI usually affects temporal lobes bilaterally, and thus memory impairment is nonspecific (Mapou, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…Most studies with patients who sustained moderate to severe TBI have found impaired memory (Blachsteni et al, 1993;Millis and Ricker, 1994;Vakil, 2005;Vanderploeg et al, 2001). In addition, recovery of learning and memory functions has been found to be slower compared to other TBI cognitive abilities (Lezak, 1979), with deficient learning and memory persisting after moderate to severe TBI (Zec et al, 2001). TBI usually affects temporal lobes bilaterally, and thus memory impairment is nonspecific (Mapou, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…Multiple memory modalities can be affected. While explicit memory impairment is well-documented (Zec et al, 2001), less is known about procedural ("how to" knowledge) learning and memory deficits in patients with TBI, with disagreement about whether these occur and to what extent (Vakil, 2005). Even less is known about the time-course of multi-session training in TBI.…”
Section: Memory Deficits In Tbimentioning
confidence: 99%
“…Because the investigators controlled for acquisition differences and for ceiling effects on recall and recognition measures, they attributed their findings to a consolidation deficit. A more rapid rate of forgetting has also been reported in other studies (Stuss et al, 1985, Zec et al, 2001, regardless of whether they controlled for acquisition differences between groups. Nevertheless, similar rates of forgetting by patient and control groups were found by DeLuca et al (2000) when groups were equated for initial levels of learning.…”
Section: Evidence For a Consolidation Deficitmentioning
confidence: 61%
“…In one study conducted an average of 3.25 years postinjury, patients with PTA greater than 3 weeks were impaired on the Logical Memory subtest of the WMS and on the delayed recall trial of the Rey Complex Figure Test compared to orthopedic controls (Bennett-Levy, 1984). Another study reported that a group that had sustained a severe TBI an average of 10 years earlier performed more poorly than a spinal cord injury group on several verbal and visual memory tests (Zec et al, 2001). Measures included the Buschke Selective Reminding Test, RAVLT, and WMS-R.…”
Section: Long-term Effects Of Tbi On Memorymentioning
confidence: 94%
See 1 more Smart Citation